Study of Optical, Structural and Morphology Properties of Tin Oxide Nanoparticles by Pulse Laser Ablation and its Effect on Bacteria Staphylococcus aureus - Saeed , Zahraa A.; Aadim, Kadhim A. (Iraqi Journal of Science, 2023)
Tin oxide (Sn) nanoparticles were prepared by pulsed laser ablation (PLA) method at different laser energies (400-700mJ). (UV, XRD, AFM, SEM, EDS) methods were employed to determine the properties of nanomaterials. The optical properties showed that the energy gap decreased with increasing laser power; the structural properties showed the relationship between density and angle; Miller’s coefficients for net angles were determined and the morphology properties showed the element’s surface shape and surface roughness. Also, Tin oxide nanoparticles with added to Staphylococcus aureus bacteria isolated from the ear and cultured by striking method on nutrient agar to know the effect of tin oxide nanoparticles on the growth of this bacteria. The results showed that tin (Sn) oxide nanoparticles had a role in decreasing the growth of bacteria on cultured media using the laser energies of (400mJ, 500mJ and 600mJ), but at an energy of 700mJ a clear zone (no growth) of bacteria on cultured media was noted, indicating 100% bacterial killing.